Microstructural evolution and deformation mechanisms in CoCrNi medium entropy alloy fabricated by additive and subtractive hybrid manufacturing - Nan Wang; Wei Yue; Shamima Sultana; YongGang Sun; TianXu Zhao; ChangYu Liu; ZeHao Li; Shuang Su; ZhiLiang Ning; Tung Lik Lee; YanMing Zhang; JianFei Sun; et al. (Virtual and Physical Prototyping, 2025)
Additive and subtractive hybrid manufacturing offers great potential for the integrated fabrication of high-performance structural components. CoCrNi MEA specimens were subjected to subtractive manufacturing (SM) immediately after additive manufacturing (AM) at elevated temperatures, forming a gradient microstructure approximately 100 µm in depth through the coupling of thermal and mechanical effects. The near-machined surface exhibited interactions between mechanical twins and stacking faults, which refined grains and promoted nanocrystals. Dynamic recrystallization (DRX) further refined the nanocrystalline structure, improving residual stress distribution and enhancing strain hardening. Three key mechanisms contributed to the enhanced properties. First, the transition from tensile to compressive residual stress introduced by surface plastic deformation effectively suppressed crack initiation and promoted ductility. Second, DRX activated under elevated temperatures homogenised the refined grain structure and improved strain compatibility. Third, the synergistic activation of stacking fault-induced plasticity, twinning-induced plasticity, and strain gradient hardening stabilised plastic flow and delayed strain localisation. Compared to specimens subjected to SM at room temperature (with ∼60 µm inhomogeneous gradient layer), subjecting the specimen to SM at an elevated temperature led to notable improvements in yield strength (25%), tensile strength (33%), and elongation (70%) over the AM-fabricated MEA specimen, demonstrating a clear synergy between strength and ductility.